Perlindungan Hukum Terhadap Pekerja/Buruh Yang Putus Hubungan Kerja Sebelum Masa Kontrak Kerja Berakhir - Chamdani, Chamdani; Endarto, Budi; Kusnadi, Sekar Ayumeida; Indrajaja, Nobella; Syafii, Syafii (Universitas Muhammadiyah Palembang, 2022)
This research is a conceptual study that aims to analyze the form of legal protection for workers who break their employment before the contract period ends by using the logic of deductive thinking with a statutory approach (statute approach). by relying on the concepts of its incarnation, views or doctrines that have existed with legal materials accessed through the internet after the enactment of Law No. 11 of 2020 concerning Job Creation. The results show that the government's constitutional obligation not only provides the widest possible employment for citizens, but also obliges to provide legal protection to every citizen to get fair treatment in the employment relationship. In the context of the provision of the rights of workers who break the employment relationship before the contract period ends if the termination of employment at the will of the employer, then the employer is obliged to pay compensation to the worker in the form of wages whose amount is calculated from the termination of the employment relationship until the end of the contract period and vice versa if the termination of employment on the will of the worker then the worker Must pay to the employer in the form of compensation in the amount of wages that will be received by workers from the will of termination of employment until the expiration of the contract period and the company is obliged to pay compensation to workers for the termination of the employment since a certain time employment agreement has been implemented by the worker.Keywords: Legal Protection; Contract Worker; Termination of Employment